Nucleic aptamer modified porous reduced graphene oxide/MoS2 based electrodes for viral detection: application to human papillomavirus (HPV) - Chekin, Fereshteh; Bagga, Komal; Subramanian, Palaniappan; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Next to graphene nanomaterials, molybdenum disulfide (MoS2) offers large surface area that can enhance its biosensing performance. In this work, we investigate the performance of glassy carbon (GC) electrodes modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS2) for the sensitive and selective detection of the L1-major capsid protein of human papilloma virus (HPV). Owing to the difficulties to perform serological assays and HPV culture efficiently, tools based on molecular recognition are becoming of great importance. We developed here an electrochemical sensor for HPV upon covalent functionalization of the electrode with an aptamer Sc5-c3, a RNA aptamer targeted against the HPV-16 L1 protein. Using differential pulse voltammetry (DPV) and an optimized sensor interface, a linear relationship between the peak current density of a redox couple such as [Fe(CN)6]4- and the concentration of HPV-16 L1 proteins in the range of 0.2-2 ng mL(-1) (3.5 pM-35.3 pM) could be reached with a detection limit of 0.1 ng mL(-1) (1.75 pM). Cross-reactivity studies demonstrated high selectivity over potential interfering species such as HPV-16 E6, opening new opportunities of the developed concept for the development of point of care devices. (C) 2018 Elsevier B.V. All rights reserved.